Well posedness and control in renewal equations with nonlocal boundary conditions. (8th June 2021) - Colombo, Rinaldo M.; Garavello, Mauro
Abstract : A large class of biological models leads to initial boundary value problems for nonhomogeneous balance laws, possibly with nonlocal boundary conditions. Here, for these equations, a general well posedness result is proved, a full set of stability estimates is provided, and sample control problems are tackled.